Zebrafish Models of Craniofacial Malformations: Interactions of Environmental Factors - Raterman, S. T.; Metz, J. R.; Wagener, Frank A. D. T. G.; Von den Hoff, Johannes W. (Frontiers in Cell and Developmental Biology, 2020)
The zebrafish is an appealing model organism for investigating the genetic (G) and environmental (E) factors, as well as their interactions (GxE), which contribute to craniofacial malformations. Here, we review zebrafish studies on environmental factors involved in the etiology of craniofacial malformations in humans including maternal smoking, alcohol consumption, nutrition and drug use. As an example, we focus on the (cleft) palate, for which the zebrafish ethmoid plate is a good model. This review highlights the importance of investigating ExE interactions and discusses the variable effects of exposure to environmental factors on craniofacial development depending on dosage, exposure time and developmental stage. Zebrafish also promise to be a good tool to study novel craniofacial teratogens and toxin mixtures. Lastly, we discuss the handful of studies on gene-alcohol interactions (GxE) using mutant sensitivity screens and reverse genetic techniques. We expect that studies addressing complex interactions (ExE and GxE) in craniofacial malformations will increase in the coming years. These are likely to uncover currently unknown mechanisms with implications for the prevention of craniofacial malformations. The zebrafish appears to be an excellent complementary model with high translational value to study these complex interactions.